The impact of the oxygen scavenger on the dose-rate dependence and dose sensitivity of MAGIC type polymer gels. (12th March 2018) - Khan, Muzafar; Heilemann, Gerd; Kuess, Peter; Georg, Dietmar; Berg, Andreas
Abstract: Recent developments in radiation therapy aimed at more precise dose delivery along with higher dose gradients (dose painting) and more efficient dose delivery with higher dose rates e.g. flattening filter free (FFF) irradiation. Magnetic-resonance-imaging based polymer gel dosimetry offers 3D information for precise dose delivery techniques. Many of the proposed polymer gels have been reported to exhibit a dose response, measured as relaxation rate Δ R 2(D), which is dose rate dependent. A lack of or a reduced dose-rate sensitivity is very important for dosimetric accuracy, especially with regard to the increasing clinical use of FFF irradiation protocols with LINACs at high dose rates. Some commonly used polymer gels are based on M ethacrylic- A cid- G el- I nitiated-by- C opper (MAGIC). Here, we report on the dose sensitivity (Δ R 2/Δ D ) of MAGIC-type gels with different oxygen scavenger concentration for their specific dependence on the applied dose rate in order to improve the dosimetric performance, especially for high dose rates. A preclinical x-ray machine ('Yxlon', E = 200 kV) was used for irradiation to cover a range of dose rates from low D ˙ min = 0.6 Gy min −1 to high D ˙ max = 18 Gy min −1 . The dose response was evaluated using R 2-imaging of the gel on a human high-field (7T) MR-scanner. The results indicate that all of the investigated dose rates had an impact on the dose response in polymer gel dosimeters, being strongest in the high dose region and less effective for low dose levels. The absolute dose rate dependence ( Δ R 2 / Δ D ) Δ D ˙ of the dose response in MAGIC-type gel is significantly reduced using higher concentrations of oxygen scavenger at the expense of reduced dose sensitivity. For quantitative dose evaluations the relative dose rate dependence of a polymer gel, normalized to its sensitivity is important. Based on this normalized sensitivity the dose rate sensitivity was reduced distinctly using an increased oxygen scavenger concentration with reference to standard MAGIC-type gel formulation at high dose rate levels. The proposed gel composition with high oxygen scavenger concentration exhibits a larger linear active dose response and might be used especially in FFF-radiation applications and preclinical dosimetry at high dose rates. We propose in general to use high dose rates for calibration and evaluation as the change in relative dose sensitivity is reduced at higher dose rates in all of the investigated gel types.